Answer:
So after reflecting over the x-axis, the equation is:
[tex]-y = x-2[/tex]
so the equation in the slope-intercept form
[tex]-y = x-2[/tex]
[tex]y=-x+2[/tex]
Here,
Step-by-step explanation:
Given the equation
[tex]y = x - 2[/tex]
Reflecting over the x-axis inverts the sign of the y-coordinate, but the sign of the x-coordinate remains the same.
So after reflecting over the x-axis, the equation is:
[tex]-y = x-2[/tex]
Now, writing the equation in the slope-intercept form
[tex]y=mx+b[/tex]
where m is the slope and b is the y-intercept
so the equation in the slope-intercept form
[tex]-y = x-2[/tex]
[tex]y=-x+2[/tex]
Here,